A pioneering undertaking to be optimized: legal transplantation and practice of the notice and takedown regime under China's Patent Law. Issue 3 (August 2018) - Zhang, Xianwei; Zhu, Xiequn
Abstract : Due to the enormous extent of the e-commerce market in China, the problem of online patent rights infringement has become more severe and has received more attention from Chinese legislators. Therefore, in the latest Draft Patent Law Amendment, the 'notice and takedown' rule originally used in copyright law has now been transplanted into patent law to tackle online patent infringement issues. In our view, because there is a clear distinction between infringement of patent right and infringement of copyright, the notice and takedown rule cannot simply be transplanted without creating an unnecessary burden on internet service providers. Based on an evaluation of court rulings of the People's Republic of China, this article will provide recommendations for improving the application of the rule.